2005
DOI: 10.1002/chin.200534001
|View full text |Cite
|
Sign up to set email alerts
|

Gold as Hydrogen. An Experimental and Theoretical Study of the Structures and Bonding in Disilicon Gold Clusters Si2Aun and Si2Aun (n = 2 and 4) and Comparisons to Si2H2 and Si2H4.

Abstract: and Si2Aun (n = 2 and 4) and Comparisons to Si2H2 and Si2H4. -The geometrical and electronic structures of the title disilicon gold clusters are characterized by photoelectron spectroscopy and ab initio density functional and coupled clusters theory calculations. The various stable isomers found for Si 2 Au 2 and Si 2 Au 4 are similar to those known for Si 2 H 2 and Si 2 H 4 , respectively. -(LI, X.; KIRAN, B.; WANG*, L.-S.; J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…The electronic binding energies of C 2 HAg n -(n=1-4) well fall within the energy range of conventional excitation lasers used in PES measurements (266 nm, 4.661 eV) [45][46][47][48]. We notice that the difference between ADE and VDE of C 2 HAg 4 -is the largest (0.73 eV).…”
Section: Electron Detachment Energiessupporting
confidence: 76%
“…The electronic binding energies of C 2 HAg n -(n=1-4) well fall within the energy range of conventional excitation lasers used in PES measurements (266 nm, 4.661 eV) [45][46][47][48]. We notice that the difference between ADE and VDE of C 2 HAg 4 -is the largest (0.73 eV).…”
Section: Electron Detachment Energiessupporting
confidence: 76%
“…There have been a relatively fewer number of studies on the silicon-doped gold clusters. One of the fascinating findings reported on the silicon-doped gold clusters is the gold–hydrogen analogy. , Recently, on the other hand, Pal et al have carried a systematic study on the structural evolution of silicon-doped gold clusters and have shown that silicon-doped gold clusters have a significantly different structure. Although the reactivity of gold clusters strongly depends on their shape and electronic distribution, , little is known about the catalytic activity of silicon-doped gold clusters that show contrastingly different structures and electronic structures as compared to the pristine gold clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen in gold has a special relevance considering the so-called gold–hydrogen analogy as established by Kiran et al, where the chemistry of the gold atom resembles that of a single hydrogen atom. Extending a step further, this Au/H analogy initially reported for mono- and disilicon gold clusters has also been extended to trisilicon gold clusters by the same authors .…”
mentioning
confidence: 99%